2009
DOI: 10.1177/0261018308098392
|View full text |Cite
|
Sign up to set email alerts
|

The `problem' of anti-social behaviour and the policy knowledge base: Analysing the power/knowledge relationship

Abstract: The high priority given to tackling anti-social behaviour in current government policy might generate an expectation that knowledge of the nature and extent of the problem would provide an empirical underpinning for policy. However, a detailed examination of the state of official 'knowledge' of the problem of anti-social behaviour shows that there are substantial gaps and ambiguities in what is known, and disjunctures between some of the claims made by government about its approach and what the official eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Prior (2009) Garrett (2007) and Gregg (2010) critiquing the methods used to undertake evaluations and the analysis and presentation of findings that exaggerate positive and progressive outcomes for households (see Batty and Flint, 2012). Similarly, Hayden and Jenkins (2014) Families programme (Communities and Local Government, 2012), with local authorities provided with indicative numbers of troubled families in their own localities.…”
Section: Introductionmentioning
confidence: 99%
“…Prior (2009) Garrett (2007) and Gregg (2010) critiquing the methods used to undertake evaluations and the analysis and presentation of findings that exaggerate positive and progressive outcomes for households (see Batty and Flint, 2012). Similarly, Hayden and Jenkins (2014) Families programme (Communities and Local Government, 2012), with local authorities provided with indicative numbers of troubled families in their own localities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen growing recognition of a dearth in knowledge around the nature and prevalence of ASB (Prior 2009) and the use and effectiveness of different interventions (Rubin et al 2006). In 2008, when this study began, little was known about: the extent, nature and impact of different ASB interventions on young people; young people's trajectories through different ASB interventions; and their journeys through prevention, ASB and youth justice strategies and sanctions.…”
Section: Research Aims and Methodsmentioning
confidence: 99%
“…In terms of research involving children and young people subject to custodial sentences, Finlay and Jones found that 'healthcare staff had noticed that several young offenders with a history of loss/bereavement in childhood or adolescence seemed particularly emotionally vulnerable' (2000, p. 569), while Phillips and Earle's (2010) ethnographic study of prisoners found it 'hard to hear' the details of bereavement and loss within the life stories of their subjects. Studies of young people subject to Anti Social Behaviour Orders (ASBOs) also confirm that many have suffered from bereavement or loss (Prior, 2009).…”
Section: Bereavement and Evidence-based Practicementioning
confidence: 99%